“Ispeak” an Application to Improve student’s speaking competencies - Maryati Salmiah; Natasya Herza Harahap (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
The rapid progress of technology in recent years has introduced innovative approaches to education, enabling educators to leverage technology for teaching. This study examines the